2020
DOI: 10.21203/rs.3.rs-37910/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of COVID-19 on poverty and living standards in Ghana: A micro perspective

Abstract: Abstract The novel Coronavirus disease 2019 (COVID-19), which has become a global epidemic, hit Ghana on 12th March 2020 and, in less than a week, increased by over 300 percent with two deaths. As of 11th June 2020, Ghana had recorded over 11,000 cases with 48 deaths. This study seeks to provide a micro-level evidence on how COVID-19 is posing a threat to some of the Sustainable Development Goals, particularly poverty and hunger… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…The various responses from our participants are largely corroborated by available evidence in the wake of the COVID-19 pandemic. For instance, the pandemic and its associated restrictions and measures have significantly increased the level of poverty in Ghanaian households and worsened living standards (Bukari et al, 2020 ). The adverse effects of the pandemic on the standard of living of religious leaders may be far-reaching considering that religious leaders cater to the needs of their church members, who call on them for financial support (Benyah, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The various responses from our participants are largely corroborated by available evidence in the wake of the COVID-19 pandemic. For instance, the pandemic and its associated restrictions and measures have significantly increased the level of poverty in Ghanaian households and worsened living standards (Bukari et al, 2020 ). The adverse effects of the pandemic on the standard of living of religious leaders may be far-reaching considering that religious leaders cater to the needs of their church members, who call on them for financial support (Benyah, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Por otro lado, haciendo referencia a las externalidades que genera el COVID-19 a nivel económico y social, tenemos a autores como Suryahadi et al (2020), quienes realizan estimaciones del impacto del COVID-19 sobre la pobreza en Indonesia, donde encontraron que la tasa de pobreza aumentará a 9.7% a finales del 2020 y recomiendan expandir los programas de protección social para la nueva población. Así mismo, en África Occidental en Ghana se habían registrado ya 48 muertes y 11 000 casos positivos, ante lo cual Bukari et al (2020) realizan un estudio que les permite identificar las amenazas que provoca el COVID-19 con el cumplimiento de los Objetivos de Desarrollo Sostenible -erradicar la pobreza y el hambre-utilizan Mínimos Cuadrados Ordinarios, modelo probit y regresiones, para identificar que la pandemia del COVID-19 aumentó la pobreza de los hogares y empeoró las condiciones de vida de la población, siendo los más afectados los habitantes acentuados en la zona rural. Además, existe una significancia estadística entre el período COVID-19 y los problemas asociados al agua.…”
Section: Revisión De La Literaturaunclassified
“…Sin embargo, los efectos de este tipo de medidas se ven reflejados en el normal desempeño de las actividades cotidianas de la sociedad. Esta situación se ha desbordado y ha afectado a todos los países, sin importar ninguna condición económica, social, cultural, geográfica, etc., pero ha afectado en mayor medida a aquellos países que registran grandes brechas sociales, tales como lo son los países en vías de desarrollo (Bukari et al, 2020).…”
Section: Introductionunclassified
“…While a number of studies have been conducted on the socio-economic and health impact of COVID-19 in other parts of the world [8][9][10][11][12][13][14][15][16][17][18][19][20][21] as well as in Ghana [22][23][24][25][26][27][28][29], a substantial number of these studies were either conceptual in nature or paid little attention to vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported that the partial lockdown in the Accra and Tema metropolis and the greater Kumasi area, which have the highest concentration of population in Ghana and were the epicentre of infection [3,30], resulted in hardships for the informal economy and the urban-slum [3]. Some of the effects were loss of jobs, income and lack of food, increase in poverty levels and fear of accessing health care [31][32][33][34]. This current study contributes to literature by employing a concurrent triangulation mixed methods design, to examine the socio-economic and health effects of COVID-19 as well as the categories of vulnerable individuals (urban-slum and rural residents) that are more susceptible to the effects of COVID-19 in Ghana.…”
Section: Introductionmentioning
confidence: 99%